Efficacy and safety of different medications compared for the treatment of postherpetic neuralgia: a network meta-analysis - Guo, Zhen; Xia, Yunfan; Zhang, Zuyong (Frontiers in Pharmacology, 2025)
BackgroundPostherpetic neuralgia (PHN) is a neuropathic pain and the most common complication of herpes zoster (HZ). Pharmacotherapy serves as the primary intervention for alleviating pain associated with PHN.MethodsElectronic databases were systematically searched to identify randomized controlled trials (RCTs) evaluating pharmacotherapy for PHN. The network meta-analysis (NMA) based on the Bayesian framework was analyzed using R4.4.1 and Stata18.0 software.ResultsA total of 38 RCTs were included in the analysis, enrolling 8,621 participants. In the Risk of Bias 2.0 (RoB 2.0) tool, nine studies (24%) were assessed as having a high risk of bias, 15 studies (39%) were rated as having some concerns, and 14 studies (37%) were assessed as having a low risk of bias. The NMA results showed that the NGX-4010 8% capsaicin patch had a statistically significant effect in terms of pain intensity (MD = −9.20, 95% CI: [−12.0, −6.60]). The secondary outcomes showed a significant effect of hydromorphone in improving sleep quality (MD = −3.8, 95% CI: [−23.0, −15.0]) and decreasing pain questionnaire scores (MD = −13.0, 95% CI: [−28.0, 2.1]). Amitriptyline plus pregabalin demonstrated the highest probability of clinical superiority (SUCRA = 0.92). The AE incidence results showed that opioids were identified as having the highest cumulative ranking (SUCRA = 0.87).ConclusionThe study showed that capsaicin patches and hydromorphone were more significant in relieving pain in PHN, whereas calcium channel modulators were more comprehensive in clinical management. The inclusion of more high-quality articles was needed to support this evidence due to quality bias in the literature.